Synthesis of tungsten carbide and tungsten disulfide on vertically aligned multi-walled carbon nanotube forests and their application as non-Pt electrocatalysts for the hydrogen evolution reaction1. Issue 28 (28th July 2015) - Lin, Jhih-Fong; Pitkänen, Olli; Mäklin, Jani; Puskas, Robert; Kukovecz, Akos; Dombovari, Aron; Toth, Geza; Kordas, Krisztian
<x xml:space="preserve">Abstract</x> Direct growth of tungsten carbide and sulfide on vertically aligned CNTs is demonstrated for a facile construction of three-dimensional electrocatalyst nanostructures.